The Quality of Service of Vehicle Plate Online Registration in Cambodia: Assessment and Perspective of Online Customers - Lor Mouy Ngich (Pusat Penelitian Ilmu Sosial dan Humaniora Kontemporer, Indonesia, 2021)
Limited evidence is presented for the evaluation of a particular online service, especially in developing countries. Cambodia introduced an online vehicle plate registration in 2017. Since then, there have not been any research studies on the quality of this public online service after the implementation. This research has two main aims: (1) to describe the quality of online vehicle plate registration and (2) to present citizens' perspectives who have experienced this online service provided by the Ministry of Public Works and Transport (MoPWT). The research employs a mix-method combining online questionnaires (100) and in-depth interviews (10) to answer the research questions regarding website design, reliability, citizen support, trust, and accessibility. The average score for all components and overall service quality is 2, suggesting that people perceive the service as having low quality. The results strengthen the influence of reliability and citizen support on the people’s perception of service quality as claimed by researchers. However, it contradicts the previous research in that website design though not well appreciated does not have much influence on the quality of service as claimed. The research also indicates some issues with the online system. Building more trust, providing better citizen support in time, and finally reducing the chances of corruption are components of services quality that should be improved to increase the number of people using the online service and increase citizen satisfaction.Online Service; Service Quality; Customers; Cambodia; Perspective; Citizen Support; Reliability